The Impact of the Implementation of the Posbindu PTM Program on the Coverage of Early Detection of Non-Communicable Diseases - Reni Aprinawaty Sirait (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Non-Communicable Diseases (NCDs) are the leading cause of death globally, including in Indonesia, which is experiencing an increasing prevalence of hypertension and diabetes. To address this challenge, the Indonesian government developed the Posbindu PTM program as an early detection effort for NCD risk factors at the community level. However, the effectiveness of the program implementation still faces various challenges in the field. Objective: This study aims to analyze the impact of the Posbindu PTM program implementation on the coverage of early detection of Non-Communicable Diseases in the working area of Merek Health Center, Karo District. Methods: This research employed a quantitative approach with a cross-sectional analytic design. Data were collected from 422 respondents who were active participants of Posbindu PTM using structured questionnaires, observations, and document reviews. Data were analyzed through univariate, bivariate (using Chi-Square tests), and multivariate analysis (using logistic regression). Results: The majority of respondents were female (60.2%) and aged 45–59 years (35.1%). The Posbindu activities were conducted ?3 times per year (68.2%), facilities and infrastructure were adequate (71.3%), cadres' competence was good (64.9%), and health workers’ involvement was high (59.5%). Coverage of blood pressure checks reached 74.4%, Body Mass Index (BMI) measurement 68.0%, random blood sugar checks 62.8%, and education on NCD risk factors 71.1%. A significant relationship was found between the program implementation and early detection coverage. Conclusion: The implementation of the Posbindu PTM program at Merek Health Center was fairly optimal and positively influenced the improvement of early NCD detection coverage. This program plays an important role in empowering communities to prevent and control NCDs through regular screening and health education.